1976
DOI: 10.1088/0022-3727/9/7/004
|View full text |Cite
|
Sign up to set email alerts
|

Integral methods of analysing electric arcs. III. Shape-factor correlation for low radiation and laminar flow

Abstract: For pt.II see ibid., vol.7, p.2232 (1974). The energy equation for the core of axisymmetric electric arcs is de- rived in terms of radial integrals. The formulation includes terms to describe the diffusive heat flux at the core boundary and the work done against viscous stress there. When the shape factors derived in Part I are evaluated for a number of different arc situations from known differential solutions, they correlate well in terms of a non-dimensional form of the heat flux. This result suggests that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The axial and radial components of are given by (9) For axisymmetric arc, the azimuthal magnetic flux density can be calculated by (10) where is the axial component of the current density and μ 0 the permeability of free space. The two components of Lorentz force are given by (11) The approximate radiation transport model of Zhang et al [10] is adopted to calculate the net radiation loss in the energy equation.…”
Section: The Governing Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The axial and radial components of are given by (9) For axisymmetric arc, the azimuthal magnetic flux density can be calculated by (10) where is the axial component of the current density and μ 0 the permeability of free space. The two components of Lorentz force are given by (11) The approximate radiation transport model of Zhang et al [10] is adopted to calculate the net radiation loss in the energy equation.…”
Section: The Governing Equationsmentioning
confidence: 99%
“…Arc modelling at that time was mainly based on the integral method [5,[7][8][9]. This method of arc analysis has achieved considerable success in predicting the arc behaviour under steady state and for relatively high currents [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…the electrode placed inside nozzle before the throat: in this case, expansion of equation ( 30) gives implying that M,CC({-Se) near the electrode. Thus the arc exhibits 'self-similar' behaviour near the electrode and g=2/0.5 (Chan 1976). The term 'self-similar' is used here to indicate that when the arc is subjected to a linear velocity gradient external flow, it has been found that all the arc '8' areas are constant.…”
Section: Initial Boundary Conditionsmentioning
confidence: 99%
“…Chan et el. (192,193) use integral methods to analyze axisymmetric arcs in laminar flow extinction gases. Arc behaviour is predicted in terms of density, velocity, enthalpy, and various shape factors.…”
Section: High Pressure Arcsmentioning
confidence: 99%